CYPRINUS CARPIO VAR. COMMUNIS, IN MIDDLE STRETCH OF RIVER GANGA AT ALLAHABAD - PATHAK, R. K.; GOPESH, A.; JOSHI, K. D.; DWIVEDI, A. C. (Journal of the Inland Fisheries Society of India, 2021)
Cyprinus carpio, commonly known as common carp, is an exotic fish species in India. Presence of this species has been reported to reduce diversity and modify local community dynamics in freshwater systems (Minns and Cooley, 2000). They are perceived as a significant ecological pest in many countries where they have been introduced (Arlinghous and Mehner, 2003) and are generally considered ecologically most detrimental of all freshwater invasive fish species (Crivelli, 1983; Zambrano et al., 2001; Dean, 2003; Koehn, 2003). Despite all these features the common carp forms the most common fishery of the world. Today many countries have extensive and intensive farming of common carp. Common carp prefers slow and stagnant water bodies, and /or silt bottoms with shell incorporations (Balon, 1995). The present study was aimed to assess on the population structure of C. carpio in the middle stretch of the Ganga river at Allahabad.